Extrasynaptic and postsynaptic receptors in glycinergic and GABAergic neurotransmission: a division of labor? - Muller, Emilie; Le-Corronc, Hervé; Legendre, Pascal (Frontiers in Molecular Neuroscience, 2008)
Glycine and GABA mediate inhibitory neurotransmission in the spinal cord and central nervous system. The general concept of neurotransmission is now challenged by the contribution of both phasic activation of postsynaptic glycine and GABAA receptors (GlyRs and GABAARs, respectively) and tonic activity of these receptors located at extrasynaptic sites. GlyR and GABAAR kinetics depend on several parameters, including subunit composition, subsynaptic localization and activation mode. Postsynaptic and extrasynaptic receptors display different subunit compositions and are activated by fast presynaptic and slow paracrine release of neurotransmitters, respectively. GlyR and GABAAR functional properties also rely on their aggregation level, which is higher at postsynaptic densities than at extrasynaptic loci. Finally, these receptors can co-aggregate at mixed inhibitory postsynaptic densities where they cross-modulate their activity, providing another parameter of functional complexity. GlyR and GABAAR density at postsynaptic sites results from the balance between their internalization and insertion in the plasma membrane, but also on their lateral diffusion from and to the postsynaptic loci. The dynamic exchange of receptors between synaptic and extrasynaptic sites and their functional adaptation in terms of kinetics point out a new adaptive process of inhibitory neurotransmission.